2019
DOI: 10.1038/s41598-019-43472-4
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock factor 1 protects germ cell proliferation during early ovarian differentiation in medaka

Abstract: The heat shock response is important for the viability of all living organisms. It involves the induction of heat shock proteins whose expression is mainly regulated by heat shock factor 1 (HSF1). Medaka ( Oryzias latipes ) is a teleost fish with an XX/XY sex determination system. High water temperature (HT) inhibits the female-type proliferation of germ cells and induces the masculinisation of XX medaka in some cases during gonadal sex differentiation. Here, we investigated the roles of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Though not well studied in the context of sex determination, heat shock factors and proteins have been implicated in female sex determination in mammals and fish, and may also play a conserved role in the ovarian pathway in P. vitticeps (79,124127). Surprisingly, only one gene associated with canonical heat shock response ( HSP40 , also known as DNAJC28 ) was differentially expressed following exposure to high temperature in stage 6 ZZf females compared to ZWf embryos (Additional file S3).…”
Section: Resultsmentioning
confidence: 99%
“…Though not well studied in the context of sex determination, heat shock factors and proteins have been implicated in female sex determination in mammals and fish, and may also play a conserved role in the ovarian pathway in P. vitticeps (79,124127). Surprisingly, only one gene associated with canonical heat shock response ( HSP40 , also known as DNAJC28 ) was differentially expressed following exposure to high temperature in stage 6 ZZf females compared to ZWf embryos (Additional file S3).…”
Section: Resultsmentioning
confidence: 99%
“…Total RNA was extracted from the gonad regions (20 pooled samples) of XX larvae at 0 dph using NucleoSpin RNA XS (Takara Bio, Shiga, Japan) according to the manufacturer’s protocol 44 . The XX larvae untreated (control), or treated with HT or cortisol from 0 dpf to 0 dph were selected by the existence of leucophores and the gonad regions containing the guts were cut out under a stereo microscope MZ (Leica Microsystems, Wetzlar, Germany) as described previously 15 .…”
Section: Methodsmentioning
confidence: 99%
“…Furukawa et al [54] shows that the HSF1 is a very important regulator in the ovarian differentiation of Medaka. They made a HSF1 knock-out animal and found that HSF1 protects the female germ cells under heat stress.…”
Section: Discussionmentioning
confidence: 99%